Evolution of fossil ecosystems - Selden, Paul (Manson Publishing Ltd, 2012)
This book, widely praised for its coverage and approach in describing and illustrating 14 well known fossil sites from around the world, is now full updated with 6 new chapters and many new colour illustrations. A beautifully illustrated study of fossil sites from different periods providing a picture of the evolution of ecosystems down the ages.
Keywords: Evolutionary paleoecology.; Fossils -- North America.; Shale.; North America.; elektronické knihy; electronic books